The Potential Role of Plants Growth Promoting Rhizobium Species from Organic Base Bio Fertilizer Production from Nitrogen Fixing Bacteria: A Sustainable Approach for Developing Countries - Silas David Emmanuel; I. M. Bugaje; E. M. Okonkwo; S. Umar; M. Tanimu; M. C. Adeyeye (Research Advances and Challenges in Agricultural Sciences Vol. 5, 2024)
Purpose: One of the challenges of globalization to developing countries is how to increase agricultural production that will take care of the rapid increase in population. This can be achieved by the use of plant growth promoting rhizobium (PGPR) which are various species of beneficial microorganisms grown in the rhizosphere, participating in nutrient cycling and the production of plant growth promoting substances. Aim: The present study highlights the potential role of plants growth promoting rhizobium species from organic base bio fertilizer production from nitrogen fixing bacteria. Methodology: Soil samples were collected from 12 sites, four from each of the study areas viz; NARICT farm land, Yankusa Land fill, and Sakadadi agricultural farm land. The total chromium content was analyzed using atomic absorption spectrophotometry (AAS). Physiochemical analysis of the contaminated and control landfills were also determined. The parameters determined were color, odor, pH, temperature, Nitrogen, % potassium and % phosphorus etc. Results: All parameters were found to be higher than the WHO limit except % Nitrogen, % Potassium and % Phosphorus that falls beyond. Further investigations were carried out to checkmate the proximate analysis of some nutritional values of Chemical fertilizer A and B as control while C for biofertilizer (treated) Most of the results computed shows there were significantly higher values in both macronutrient and micronutrient in Biofertilizer(C) production than those of the Chemical fertilizer (A and B). In view of the current investigation, bacteria isolate like those of (Rhizobium sp.) namely; Rhizobium japonicum, Rhizobium lupine etc., were isolated as nitrogen fixing bacteria from root nodules of soya bean. Thus identification, and characterization rhizobia sp. for the production of biofertilizer in selective modified (MYEMA) through which propagation of bacteria mass cells were accentuated in-situ: To this effect, the propagated mass cells of the bacteria were therefore meticulously and circumspectly mixed with multiple carrier base materials; for further utilization in the soils to increase its nutrient quality naturally after combining it with the soil. For nitrogen is one of the important components which acts as a building blocks of most biomolecules, but this inert nitrogen cannot be utilized by plants so the Rhizobium bacteria helps to fix the atmospheric nitrogen to ammonia which can be utilized by plants. Novelty: In view of this study the production of biofertilizer from nitrogen fixing bacterial strains as well as utilizing them in the organic farming is a well come development that would protect and sub guide both develop and developing countries from decay as well as maintaining self-reliance (prestige)( no more Aligo Dangote Chemical fertilizer recipe( unhealthy to human organelles) that is only depended on mass importation, and thereby given credit to other men countries. Thus, naira value has drastically fallen down 1 US Dollar is equivalent to 900 naira only or so.